Health-related word recognition and pronunciation by patients in Gauteng, South Africa in English and native languages - Boitumelo Ditshwane; Zelda Janse van Rensburg; Wanda Jacobs (AOSIS, 2024)
Background: Low health literacy has been found to affect people's ability to take care of their own health and follow the principles of disease prevention. Incomprehension of health education and healthcare instructions may lead to poor health outcomes. Aim: The aim of the study was to describe and compare a sample of primary healthcare patient's ability to recognise and pronounce health-related words in English and in his or her native language. Setting: The study was conducted in 12 primary healthcare (PHC) clinics in Gauteng, South Africa. Methods: A prospective, quantitative, comparative research design using a survey method was used to assess the ability to recognise and pronounce health-related words of 401 respondents using the REALM-R (SA) tool. Results: Most respondents were 18-29 years (32%) and 30-49 years (53%) old. More than half (54%) of the respondents have completed grade 12 schooling. Adequate English health-related word recognition and pronunciation levels were at 19.5%, while native health-related word recognition and pronunciation levels were far better, ranging between 55.6% and 97.0%. Conclusion: Respondents showed better word recognition and pronunciation of the health-related words in their native language than in English. Providing health information in the patient's native language and on their level of understanding may therefore improve patient health outcomes. Contribution: The study is the first of its kind to determine word recognition and pronunciation of health-related words in English and a native language of South African PHC patients. Knowing this may assist healthcare professionals to give health education and instructions on the patient's level of understanding.